Draft Sixth Five Year Plan 1980-85 (Volume I-Review) Uttar Pradesh - Planning Commission (Planning Commission, 1980)
Background and goals—The Fifth Five Year Plan was originally intended to cover the period from 1974-75 to 1978-79. However, in October 1977, the then Planning Commission and the Government of India decided to terminate the Fifth Plan on 31st March, 1978, and to formulate a new Five-Year Plan for 1978—83. Simultaneous to the decision to terminate the plan one year in advance, it was also decided to introduce some basic changes in the planning process which would permit of greater flexibility and timely corrections for unforeseen events. The name given to these changes was the methodology of rolling plans.
Uttar Pradesh Planning Department